(untitled) (Unilorin Journal of Lifelong Education, 2025)
Abstract The aim of this paper is to review three major existing agricultural programmes in Zamfara State and examine their achievements and challenges in order to propose options for improvement in the state. This is necessary in order to enhance food security and reduce poverty to a minimum level in the state. The programmes reviewed were Zamfara State Integrated Development Programme (ZASIDEP), Comprehensive Agricultural Revolution Programme (ZACAREP) and International fund for Agricultural Development (IFAD). ZASIDEP aims are to revitalize agriculture, provide marketing strategies and education for the masses on the role of agriculture in wealth creation among others. ZACAREP on the other hand was designed to achieve increase in crop production, crop intensification, capacity building, and development of farmers association among others; while IFAD goals are to invest in people and empower them to increase their food security, improve the nutrition of their families and improve their income. Some of these aims were not yet achieved due to some factors such as insecurity, lack of political will by successive governments and large portion of ungoverned spaces where government presence is not yet felt among others. The researcher suggests that insecurity should be addressed and low interest rate loans provided for farmers. Furthermore, terrorism should be reduced within the state and strong political will be exhibited in all territories in the state where governments presence is not felt.